Three Dimension Scanning using Infrared Coded Light (ELEKTRIKA- Journal of Electrical Engineering, 2020)
In this competitive market, reverse engineering is introduced to shorten a new product development time by digitizing an existing product for rapid redesign. In this project, a low cost and standalone 3D scanner is being developed to achieve this purpose. Research is done comparing advantages and limitation of different hardware and method for 3D scanning. Scanner is assisted by automated rotating and illumination scanning platform to improve its performance. Software is developed for scanning of object using a Red-Green-Blue-Depth (RGBD) camera. The scanned result is processed and refined using global and local registration method. Poisson surface reconstruction is performed on the processed point clouds for generating triangular mesh. This scanner able to scan the object with the accuracy up to 5mm with computational time around 25 minutes.